Wave Transmission Analysis on Hexagonal Shape Floating Breakwater - Sujantoko Sujantoko; Haryo Dwito Armono; Wisnu Wardhana; Dedi Kurniawan (International Journal of Offshore and Coastal Engineering, 2021)
Coastal areas have many benefits for activities, such as port construction, fishing activities, recreation areas, resource utilization, alternative energy-producing places, etc. However, many factors limit this use due to water wave activity, such as storm surges and the potential for tsunamis. These factors also cause abrasion and coastal erosion that can damage the coastal environment. To overcome this problem, it can be done by building a coastal protective structure, one of which is a floating breakwater. In this study, analysis of wave transmission on a hexagonal floating breakwater will be carried out to determine the effectiveness of its performance. The wave transmission test on the floating breakwater was carried out with variations of irregular waves (Jonswap spectrum) and mooring angles. The position of the wave probe is set at 100 cm and 220 cm behind the structure. The largest transmission coefficient occurs at a mooring angle of 30o in both scenario 1 and scenario 2. The smallest transmission coefficient value is at an angle of 60o in both scenarios of wave probe placement. The plotting results show that the transmission coefficient is directly proportional to the period and height of the incident wave and vice versa the transmission coefficient is inversely proportional to the steepness of the wave